Exudates segmentation using inverse surface adaptive thresholding - Haniza, Yazid; Hamzah, Arof, Dr.; Hazlita, Mohd Isa, Dr. (Elsevier B.V., 2013)
Link to publisher's homepage a http://www.journals.elsevier.com/measurement/